Fluoroscopic Categorization of Cementless Acetabular Component Positioning - Sadowitz, Peter M.; Karlin, William M.; Lirtzman, Ross A.; Kowaleski, Michael P. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objectives The purpose of this study was to evaluate a fluoroscopic method of angle of lateral opening (ALO) categorization based on identification of the visible portion of a pre-existing, circular recess within the metal shell of the BioMedtrix BFX acetabular component, which projects as an ellipse at clinically relevant ALO values. Our hypothesis was that there will be an association between the actual ALO and the categorization of ALO based on identification of the visible portion of the elliptical recess on a lateral fluoroscopic image at clinically relevant values.Study Design A custom plexiglass jig was fitted with a two-axis inclinometer and a 24 mm BFX acetabular component attached to its tabletop. Fluoroscopic reference images were obtained with the cup positioned at an ALO of 35, 45 and 55 degrees with a fixed 10 degrees of retroversion. Thirty study fluoroscopic images (10 images at each ALO) were obtained based on randomization at an ALO of 35, 45 and 55 degrees (±0.5 degrees) with 10 degrees of retroversion. The order of the study images was randomized, and a single, blinded observer categorized the 30 study images as representing an ALO of 35, 45 or 55 degrees by comparison to the reference images.Results Analysis showed perfect (30/30) agreement with a weighted kappa coefficient of 1 (95% confidence interval: −0.717 to 1).Clinical Relevance The results demonstrate that accurate categorization of ALO can be achieved using this fluoroscopic method. This method may prove to be a simple but effective method of estimating intraoperative ALO.
Keywords: total hip arthroplasty; angle of lateral opening; acetabular component; fluoroscopy; canine